Narwhal and Jelly : Happy Narwhalidays - Book 5 5, Happy Narwhalidays - Clanton, Ben, 1988- ([Toronto, Ontario] : Tundra, 2020)
"It's the festive season in the world wide waters, and Narwhal is looking forward to cozying up with a good book, singing and partying with his pod pals, and enjoying some warm waffle pudding. But most of all he's excited about the arrival of the Merry Mermicorn"--Publisher marketing.
'Tis the season -- The perfect present -- The mean green jelly bean -- The Merry Mermicorn!
Keywords: Christmas -- Comic books, strips, etc; Narwhal -- Comic books, strips, etc; Jellyfishes -- Comic books, strips, etc; Marine animals -- Comic books, strips, etc; Ocean -- Comic books, strips, etc; Christmas -- Fiction; Narwhal -- Fiction; Jellyfishes -- Fiction; Marine animals -- Fiction; Ocean -- Fiction; Cartoons and comics; Comics (Graphic works)